2008
DOI: 10.1074/jbc.m802404200
|View full text |Cite
|
Sign up to set email alerts
|

Control Over the Contribution of the Mitochondrial Membrane Potential (ΔΨ) and Proton Gradient (ΔpH) to the Protonmotive Force (Δp)

Abstract: The protonmotive force across the inner mitochondrial membrane (⌬p) has two components: membrane potential (⌬⌿) and the gradient of proton concentration (⌬pH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…The flux was then increased, either with the proton ionophore CCCP or by adding glutamine to the suspension medium, and then extrapolating 2⌬E s /⌬P to values at zero flux (equilibrium) at which point it is equal to the proton pumping stoichiometry. The relationship between ⌬G and flux is not necessarily linear, but the results presented here show that linearity is a good approximation over the range of fluxes studied and justifies the use of a linear force flux relationship in models of the electron transport chain (21). When this was carried out, it was found that the H ϩ /2e Ϫ stoichiometry was 4.4 Ϯ 0.1 and 4.1 Ϯ 0.1 for HL-60 and RAW cells, respectively, when flux was increased from the oligomycin-inhibited state with CCCP, and 4.0 Ϯ 0.1 for RAW cells when flux was increased by adding glutamine to cells cultured overnight in the absence of glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…The flux was then increased, either with the proton ionophore CCCP or by adding glutamine to the suspension medium, and then extrapolating 2⌬E s /⌬P to values at zero flux (equilibrium) at which point it is equal to the proton pumping stoichiometry. The relationship between ⌬G and flux is not necessarily linear, but the results presented here show that linearity is a good approximation over the range of fluxes studied and justifies the use of a linear force flux relationship in models of the electron transport chain (21). When this was carried out, it was found that the H ϩ /2e Ϫ stoichiometry was 4.4 Ϯ 0.1 and 4.1 Ϯ 0.1 for HL-60 and RAW cells, respectively, when flux was increased from the oligomycin-inhibited state with CCCP, and 4.0 Ϯ 0.1 for RAW cells when flux was increased by adding glutamine to cells cultured overnight in the absence of glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative phosphorylation model was adapted from the model of Dzbek & Korzeniewski (). The dependences of Complex I on NADH and ubiquinone, and of Complex III on reduced ubiquinone and cytochrome c were newly added to fit the model to experimental time courses reported by Bose et al .…”
Section: Methodsmentioning
confidence: 99%
“…Electron transfer is coupled to the pumping of protons through complexes I, III, and IV into the intermembrane space establishing the PMF. The PMF is a combination of both an electrical (DC) and chemical gradient (DpH) (with DpH comprising $10% of the PMF) [31]. Using the PMF, ATP synthase drives ATP production, which is then used to support cellular work.…”
Section: Reviewmentioning
confidence: 99%